Multicenter Retrospective Analysis of Dorsal Root Ganglion Stimulator Placement Using Intraoperative Neuromonitoring in Asleep Patients During Early Periods of Adoption. Issue 4 (5th October 2020) - Falowski, Steven M.; Deer, Tim; Tubic, Goran; Mehta, Pankaj
Abstract: Objectives: Intraoperative neuromonitoring (IONM) has been used in the implantation of spinal cord stimulation for both safety and confirmation of lead placement. It is less well defined in its use for dorsal root ganglion (DRG) stimulator placement. Materials and Methods: This is a retrospective analysis of 304 leads placed in 93 patients undergoing DRG stimulation therapy with its placement utilizing IONM in asleep patients by four implanting physicians in four separate centers. The first year, or early adoption period, of placements for each site was chosen as the included cases to evaluate. Results: There were a total of 14 IONM alerts across the 304 lead placements. There were two complications, no permanent or severe adverse events, and no revisions. All alerts led to a change in approach as a corrective action. The two complications were a patient requiring a blood patch for an undetected CSF leak, while the other was a generator site seroma that resolved with conservative care. A single patient experienced transient calf paresthesia's in the post‐operative period. Conclusion: This retrospective series demonstrates the utility and accuracy of IONM in not only confirming proper dorsal placement of a DRG electrode but also in maintaining a low adverse event profile. It further demonstrates that its utility in the real world with new users can be safe and accurate with an ease of integration.